2022
DOI: 10.1155/2022/3103241
|View full text |Cite
|
Sign up to set email alerts
|

Handwashing Practice among Elementary Schoolchildren in Urban Setting, Mongolia: A School‐Based Cross‐Sectional Survey

Abstract: The designations employed and the presentation of the material in this publication do not imply the expression of any opinion whatsoever on the part of the World Health Organization concerning the legal status of any country, territory, city or area or of its authorities, or concerning the delimitation of its frontiers or boundaries. Dotted lines on maps represent approximate border lines for which there may not yet be full agreement. ICONTENTS CONTENTS PART I. REVIEW OF SCIENTIFIC DATA RELATED TO HAND HYGIENE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 604 publications
0
4
0
Order By: Relevance
“…In Mongolia, a study was conducted by Enkhbat et al, and reported that handwashing practice among pupils for both key occasions was found to be 50.1%. The results indicate a significant association between the female gender (AOR = 0.56, 95% CI = 0.45, 0.70), number of siblings (AOR = 0.72, 95% CI = 0.61, 0.80), and the presence of handwashing facilities at school (AOR = 1.15, 95% CI = 0.86, 1.42) 32 . According to the data, a mere 34% of students engage in the practice of handwashing with soap while at school.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…In Mongolia, a study was conducted by Enkhbat et al, and reported that handwashing practice among pupils for both key occasions was found to be 50.1%. The results indicate a significant association between the female gender (AOR = 0.56, 95% CI = 0.45, 0.70), number of siblings (AOR = 0.72, 95% CI = 0.61, 0.80), and the presence of handwashing facilities at school (AOR = 1.15, 95% CI = 0.86, 1.42) 32 . According to the data, a mere 34% of students engage in the practice of handwashing with soap while at school.…”
Section: Discussionmentioning
confidence: 98%
“…According to the data, a mere 34% of students engage in the practice of handwashing with soap while at school. The primary factors contributing to the omission of handwashing include the unavailability of soap, accounting for 23.9% of cases, the absence of a sink facility, which constituted 14.5% of instances, and the substitution of hand sanitizer, which accounted for 19.7% of occurrences 32 . In the Nigerian context, a significant majority of respondents, specifically 386 individuals (representing 96.5% of the sample), engage in the practice of handwashing mostly after consuming meals 33 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The importance of schools in controlling the transmission of diseases has been widely discussed, especially due to the new pandemic caused by the coronavirus (SARS-CoV-2), which causes Covid-19 (8,9) . Current evidence points out that the virus that causes COVID-19 is transmitted through respiratory droplets or by contact, when contaminated hands touch the mucous membranes of the mouth, nose or eyes.…”
Section: Introductionmentioning
confidence: 99%